Opioidergic and dopaminergic manipulation of gambling tendencies: a preliminary study in male recreational gamblers - Porchet, Roseline; Boekhoudt, Linde; Studer, Bettina; Gandamaneni, Kumar; Rani, Nisha; Binnamangala, Somashekar; Muller, Ulrich; Clark, Luke (Frontiers in Behavioral Neuroscience, 2013)
Gambling is characterized by cognitive distortions in the processing of chance and skill that are exacerbated in pathological gambling. Opioid and dopamine dysregulation is implicated in pathological gambling, but it is unclear whether these neurotransmitters modulate gambling distortions. The objective of the current study was to assess the effects of the opioid receptor antagonist naltrexone and the dopamine D2 receptor antagonist haloperidol on gambling behavior. Male recreational gamblers (n = 62) were assigned to receive single oral doses of naltrexone 50 mg, haloperidol 2 mg or placebo, in a parallel-groups design. At 2.5 h post-dosing, participants completed a slot machine task to elicit monetary wins, “near-misses,” and a manipulation of personal choice, and a roulette game to elicit two biases in sequential processing, the gambler's fallacy and the hot hand belief. Psychophysiological responses (electrodermal activity and heart rate) were taken during the slot machine task, and plasma prolactin increase was assessed. The tasks successfully induced the gambling effects of interest. Some of these effects differed across treatment groups, although the direction of effect was not in line with our predictions. Differences were driven by the naltrexone group, which displayed a greater physiological response to wins, and marginally higher confidence ratings on winning streaks. Prolactin levels increased in the naltrexone group, but did not differ between haloperidol and placebo, implying that naltrexone but not haloperidol may have been functionally active at these doses. Our results support opioid modulation of cognition during gambling-like tasks, but did not support the more specific hypothesis that naltrexone may act to ameliorate cognitive distortions.